Employment of ICT Specialists in the EU (2000-2012) - Anna Sabadash (European Commission, Joint Research Centre (JRC), 2014)
This study examines the evolution of the number of ICT-skilled workers employed in industry sectors in the EU28 over the period 2000-2012. Data are taken from the Eurostat Labour Force Statistics. It introduces a novel definition of ICT specialists that combines occupations and skills taxonomies. For the period prior to the introduction of the Standard Classification of Occupations (ISCO-08) it starts from the OECD definition but includes a wider range of ICT occupations. From 2011 onwards it adopts the thematic view for ICT occupations proposed by the ILO (2012). It confirms that employment of ICT specialists in the EU27 has been resilient to the economic downturn and uncertainty in global labour markets, and was able to maintain a growth path of 4.3% per year over the period 2000-2012, more than 7 times higher than average growth of total employment over the same period. Though ICT employment evolved cyclically it never turned negative. This rapid growth in ICT employment confirms the increasing importance of ICT technologies in the global economy.
Keywords: J24; 330; Employment; ICT skills